Death and overcoming it - Gagaev, Andrey A.; Gagaev, Paul A. (Opción, 2019)
The article researches the problem of death and its overcoming. The methodology is represented by the mythological representation of the past, as well as by the perspective visions of Russian religious philosophers of the 19th century, naturalistic views of the 20th century, cosmological and anthropological beliefs of our time, and the concept of substrate reflection. As a result, life as a nonrandom variable and consciousness as natural (universal) are opposed to death in its everyday sense. In conclusion, death is not the end of the being of human spirituality. Death is a transition from life to another state.